Two new sterol derivatives isolated from the endophytic fungus Aspergillus tubingensis YP-2. Issue 19 (2nd October 2021) - Yu, Shui; Zhu, Yuan-Xing; Peng, Cheng; Li, Jiyang
Abstract: Two new sterol derivatives, namely ergosterimide B (1 ) and demethylincisterol A5 (2 ), along with eleven known metabolites (3–13 ), were isolated from the rice fermentation culture of Aspergillus tubingensis YP-2. The chemical structures were elucidated by detailed NMR and MS spectroscopic data and by comparison with reported data. Newly isolated compound 2 and known compound 3 were evaluated for their cytotoxicities against the A549 and HepG2 cell lines. Compound 2 showed weak activities with IC50 values of 11.05 and 19.15 μM, respectively, while 3 exhibited cytotoxicities with IC50 values of 5.34 and 12.03 μM, respectively, against the tested cell lines. Graphical Abstract: UF0001